2017
DOI: 10.1155/2017/9640756
|View full text |Cite
|
Sign up to set email alerts
|

The Comparison of the Surgical Outcome for the Full-Thickness Macular Hole with/without Lamellar Hole-Associated Epiretinal Proliferation

Abstract: Aims To compare the surgical outcome of pars plana vitrectomy (PPV) for full-thickness macular hole (FTMH) with and without lamellar hole-associated epiretinal proliferation (LHEP). Methods This retrospective study included 158 eyes of 158 patients with FTMH treated with PPV. The following variables were analyzed: sex, age, preoperative best corrected visual acuity (pre-BCVA), BCVA 6 months after the surgery (6M-BCVA), the axial length of eye, the minimum diameter of FTMH, the diameter of basal side of FTMH, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 12 publications
7
34
0
Order By: Relevance
“…According to the results of present study, less BCVA could be regained in patients with LHEP after surgery compared with those without LHEP. This result is in consistence with most of the previous studies, which also found LMH or FTMH eyes with LHEP had worse visual outcome after surgery [8,13,14,20]. This may be because the destroy of retina was severer in eyes with LHEP than without LHEP.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…According to the results of present study, less BCVA could be regained in patients with LHEP after surgery compared with those without LHEP. This result is in consistence with most of the previous studies, which also found LMH or FTMH eyes with LHEP had worse visual outcome after surgery [8,13,14,20]. This may be because the destroy of retina was severer in eyes with LHEP than without LHEP.…”
Section: Discussionsupporting
confidence: 90%
“…By reading the titles and abstracts, 10 researches related to LHEP and surgery outcomes were reserved. Two studies included patients with FTMH were excluded [8,9], and a study recruited LMH patients with high myopia was also excluded [10]. Meanwhile, two study with incomplete information were excluded [11,12].…”
Section: Characteristics Of the Available Studiesmentioning
confidence: 99%
“…By reading the titles and abstracts, 14 papers on LHEP reporting surgical outcomes were identified. Then, the full texts of all articles were read, and 6 of them were discarded because they included patients with FTMH [8,9], recruited LMH patients with high myopia [10], had incomplete information [11,12] or were an observational study without surgery [3]. Finally, eight studies with 176 eyes without LHEP and 173 eyes with LHEP were included [13][14][15][16][17][18][19][20].…”
Section: Characteristics Of the Available Studiesmentioning
confidence: 99%
“…Besides, previous studies also indicated that LMH or FTMH eyes with LHEP had worse visual outcomes after surgery [8,13,14,24], probably attributable to the severer destruction of the retina in eyes with LHEP than without LHEP. However, there are also some studies reported similar surgery outcomes of eyes with and without LHEP [10,12,15,16].…”
Section: Discussionmentioning
confidence: 99%
“…By reading the titles and abstracts, 14 papers on LHEP reporting surgical outcomes were identi ed. Then, the full texts of all articles were read and 6 of them were discarded because they included patients with FTMH [8,9], recruited LMH patients with high myopia [10], had incomplete information [11,12] or was an observational study without surgery [3]. Finally, eight studies with 176 eyes without LHEP and 173 eyes with LHEP were included [13][14][15][16][17][18][19][20].…”
Section: Characteristics Of the Available Studiesmentioning
confidence: 99%